2017
DOI: 10.1038/s41598-017-04959-0
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of phosphorus uptake in maize plants by mycorrhizosphere bacteria

Abstract: A major challenge for agriculture is to provide sufficient plant nutrients such as phosphorus (P) to meet the global food demand. The sufficiency of P is a concern because of it’s essential role in plant growth, the finite availability of P-rock for fertilizer production and the poor plant availability of soil P. This study investigated whether biofertilizers and bioenhancers, such as arbuscular mycorrhizal fungi (AMF) and their associated bacteria could enhance growth and P uptake in maize. Plants were grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
104
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(115 citation statements)
references
References 70 publications
3
104
0
2
Order By: Relevance
“…There is increasing evidence that AM fungi recruit Pi‐solubilizing bacteria (PSB) that secrete organic acid chelators for mobilization of Pi from sparingly soluble salts and/or phosphatases for mineralization of Po (Ordoñez et al ., ; Zhang et al ., ; Battini et al ., ). In the presence of a PSB, R. irregularis released substantial organic carbon that triggered bacterial growth and thus Po mineralization (Zhang et al ., ).…”
Section: Foraging For Phosphatementioning
confidence: 97%
See 1 more Smart Citation
“…There is increasing evidence that AM fungi recruit Pi‐solubilizing bacteria (PSB) that secrete organic acid chelators for mobilization of Pi from sparingly soluble salts and/or phosphatases for mineralization of Po (Ordoñez et al ., ; Zhang et al ., ; Battini et al ., ). In the presence of a PSB, R. irregularis released substantial organic carbon that triggered bacterial growth and thus Po mineralization (Zhang et al ., ).…”
Section: Foraging For Phosphatementioning
confidence: 97%
“…Pi uptake and translocation of R. irregularis were stimulated in the presence of a Streptomyces sp. isolated from R. irregularis spores, which in turn increased Pi acquisition of the host maize (Battini et al ., ). These experiments were of course conducted under sterilized conditions.…”
Section: Foraging For Phosphatementioning
confidence: 97%
“…While there is evidence of movement from the recalcitrant forms of P to more bioavailable forms with land use management and time (González Jiménez et al, 2019), recent research has found that additions of elements such as silicon (Schaller et al, 2019), arbuscular mycorrhizal fungi (Battini et al, 2017), or phosphate solubilizing bacteria (Adnan et al, 2017) positively affect P mobilization but, in the case of phosphate solubilizing bacteria, may be affected by external factors such as pH and calcium content (Zheng et al, 2019). …”
Section: Increasing Demand For Biomass: the Need For Sustainable Intementioning
confidence: 99%
“…bacteria [5] or mycorrhizospheric [9]. They support mycorrhiza and plants by producing plant growth promoting effects, nitrogen fixation, P-solubilization, phytohormones, siderophores and antimicrobials, etc.…”
mentioning
confidence: 99%
“…They support mycorrhiza and plants by producing plant growth promoting effects, nitrogen fixation, P-solubilization, phytohormones, siderophores and antimicrobials, etc. [5]. There are countless such interactions in and around plant roots that enhances ultimate uptake of phosphorus by plants.…”
mentioning
confidence: 99%